AN OVERVIEW OF 1,5-BENZOTHIAZEPINES - PRIYANKA RANI; DHARMA KISHORE (International Journal of Pharma and Bio Sciences, 2013)
1,5-Benzothiazepine scaffold is an important class of heterocycles and has featured in a number of clinically used drugs. Compounds bearing 1,5-benzothiazepine moiety shows a broad spectrum of biological activities such as CNS-acting agents, anti-HIV and anticancer drugs, angiotensin converting enzyme inhibitors, antimicrobial, calmodulin antagonists, bradykinin receptor agonists, as well as Ca2+ blockers.